2019
DOI: 10.3917/reco.703.0375
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variable Choice in Ricardian Studies of European Agriculture

Abstract: Distribution électronique Cairn.info pour Presses de Sciences Po. © Presses de Sciences Po. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…From Figure A4 in Appendix B, we find that our model results are not robust to replacement of the climate variables. This is in line with previous study results, which state that using growing season climate variables underestimates the importance of cold temperatures (Vaitkeviciute et al, 2019).…”
Section: Alternative Meteorological Variablessupporting
confidence: 93%
See 2 more Smart Citations
“…From Figure A4 in Appendix B, we find that our model results are not robust to replacement of the climate variables. This is in line with previous study results, which state that using growing season climate variables underestimates the importance of cold temperatures (Vaitkeviciute et al, 2019).…”
Section: Alternative Meteorological Variablessupporting
confidence: 93%
“…The responses are slightly enlarged because increasing the heatwave intensity does not only affect the event frequency, but also the magnitude of heatwaves (Test 1 in Appendix B). Some Ricardian studies use total degree days and precipitation over the growing season rather than seasonal temperatures and precipitation (Massetti et al, 2016;Vaitkeviciute et al, 2019). The degree days variable is obtained by taking the sum of all daily temperatures exceeding 8°C over the growing season (April-September).…”
Section: Alternative Meteorological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Massetti, Mendelsohn and Chonabayashi (2016) show that the growing degree-days variable offers a compact alternative compared to seasonal variables, regressing farmland values (or SVi or NRi) on monthly or growing season climate data will have generated correlation issues (Vanschoenwinkel, Mendelsohn and Van Passel, 2016) Therefore, climate data were averaged into four seasons since agronomic and Ricardian studies acknowledged that seasonal temperature and precipitation have a significant impact on farm productivity (see Mendelsohn and Dinar (2009)). Moreover, in at the European continental scale, the use of growing degree-days variable as implemented by Vaitkeviciute, Chakir and Van Passel (2019) brought to the similar conclusions as founded by Van Passel, where seasonal climate variables were used. Linear and quadratic terms were introduced for both temperature and precipitation since previous studies demonstrated the non-linear relationship between climate and land values Dinar, 2003, Mendelsohn, Nordhaus andShaw, 1994).…”
Section: = ∫mentioning
confidence: 58%
“…They reported that irrigated farms are more sensitive to temperature-level fluctuations and the rain-fed ones are sensitive to changes in precipitation. The application of the Ricardian model with panel data on European agriculture by [48] also confirmed that the impact of climate change varies across the different regions of Europe and in the future. A panel data employment of Ricardian model carried out in Hungary [49] assessed that the responsiveness of agricultural production varies between short-run and long-run time horizons and the different agro-ecological zones of the country.…”
Section: Literature Reviewmentioning
confidence: 65%